Pelatihan Paduan Suara Untuk Meningkatkan Kemampuan Bernyanyi Pada Siswa di SMP Negeri 8 Banda Aceh - Samsuri Samsuri; Yuli Astuti (Jurnal Informasi Pengabdian Masyarakat, 2024)
One of the Lectures obligations in the Tri Dharma college is to carry out community service. Lecturers and students' community service makes a good and important contribution, one of which is to support quality education. One of the problems that caused this service to be carried out was the lack of students' ability to sing in a choir and the lack of ability of arts and culture teachers to share their voices at SMP Negeri 8 Banda Aceh. So the aim of this service is to improve students' singing abilities in a choir format and the insight of arts and culture teachers in teaching singing in a choir format at SMP Negeri 8 Banda Aceh. The training method is carried out using drill and demonstration methods. The results of the training in this service are an increase in students' vocal technique abilities in choral singing and an increase in the understanding and ability of arts and culture teachers at SMP Negeri 8 Banda Aceh in training choirs.